Seychelles : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper discusses measures to enhance resilience to climate and natural disasters in Seychelles. Rising sea levels, changing rainfall patterns, increasingly intense and frequent tropical cyclones, and massive coral bleaching are compounding economic and social risks in Seychelles. A policy mix focused on combining adaptation and mitigation strategies is ideal for Seychelles. Such policies should not only be aligned with Seychelles' Nationally Determined Contribution, but also with the technical and financial capacity of the government. Experience from other small states suggests that small policy changes can still have a significant impact. To the extent adaptation and mitigation measures are inadequate, insurance policies and innovative financial instruments need to be exploited further.